The anti-inflammatory and antioxidant effects of astaxanthin as an adjunctive therapy in community-acquired pneumonia: a randomized controlled trial - Youssef, Fatma Makram; Ateyya, Hayam; Hanna Samy, Amir Eskander; Elmokadem, Eman Mohamed (Frontiers in Pharmacology, 2025)
BackgroundCommunity-acquired pneumonia (CAP) is a leading cause of morbidity and mortality worldwide, particularly in low- and middle-income countries. Oxidative stress and excessive inflammation contribute significantly to disease progression and severity. Astaxanthin (ASX), a potent antioxidant and anti-inflammatory carotenoid, has demonstrated protective effects against oxidative damage and immune dysregulation in various conditions. However, its potential role as an adjunctive therapy in CAP remains underexplored. This study aims to evaluate the effects of ASX supplementation on inflammatory cytokines, and clinical outcomes in patients with CAP.Patients and methodsA prospective, randomized, double-blind, placebo-controlled study was conducted, in which adult patients diagnosed with CAP were enrolled and assigned to receive either 12 mg/day ASX or a placebo in addition to standard antibiotic therapy for 7 days. Inflammatory markers, including interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-α), and interleukin-10 (IL-10), were measured at baseline and post-treatment. Secondary outcomes included Sequential Organ Failure Assessment (SOFA) and Acute Physiology and Chronic Health Evaluation II (APACHE II) scores, as well as length of hospital stay.ResultsA total of 80 patients (40 per group) completed the study. Patients receiving ASX exhibited significant reductions in pro-inflammatory cytokines compared to the placebo group. Notably, IL-6 and TNF-α levels were significantly lower in the ASX group at the end of the study (P < 0.05). Additionally, SOFA and APACHE II scores showed greater improvements in ASX-treated patients, suggesting a potential role in mitigating disease severity. Although the ASX group had a shorter hospital stay than the placebo group, the difference was not statistically significant (P > 0.05).ConclusionASX supplementation as an adjunct to standard CAP treatment significantly reduced inflammation while improving disease severity scores. ASX was found to be safe and well-tolerated. These findings highlight its potential therapeutic role in CAP management, warranting further investigation in larger, long-term clinical trials to confirm its benefits and establish optimal dosing strategies.Clinical Trial Registrationhttps://clinicaltrials.gov/study/NCT06334874, identifier NCT06334874.